Employer branding on social media to engage Generation Z - Carbajal-Cribillero, Meredhit (2022)
Organizations compete to attract and retain top talent and differentiate themselves from their competitors; they work on employer branding strategies. This study analyzed how organizations should communicate their employer brand in social media to attract Generation Z talent. This is a qualitative research with a phenomenology design. The research technique used was the semi-structured interview. Twenty university students and graduates of business or engineering schools were interviewed; they participated on a voluntary basis. This study reveals that participants apply to an organization for the following reasons: salary, work environment, reputation, benefits, and career path. Regarding social media, the interviewees’ favorites are LinkedIn and Instagram. In relation to social media content, companies should keep in mind that Generation Z not only wants to see job offers but also to learn more about them, specifically their characteristics, as this will increase their desire to become a part of them, and in some cases, may even be decisive in accepting an offer.